Bacteriocin: A potent therapeutic weapon used as an alternative to antibiotics - Vidya Chauhan (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
Bacteriocin has proved its potential as an alternative therapeutic molecule. The discovery of bacteriocin has been a miracle to combat Antibiotic Resistance including both multidrug-resistant and chronic bacterial infections. They are ribosomally synthesised Anti-Microbial Protein (AMP), produced by bacteria [1,2]. Many species of bacteria develop this antimicrobial defence for self-preservation and competitive advantage. In comparison to antibiotics bacteriocin are sensitive to proteases and being undisruptive for human consumption [3]. Bacteriocins are small cationic (30-60 amino acids), membrane-permeabilizing peptides produced by Gram-positive (small- 2-6kDa)/negative (large- >10kDa<20kDa) bacterial species. Bacteriocins of Gram-negative bacteria are usually released through cell lysis often dependent on SOS regulation. Gram-positive bacteria follow self-regulated and dedicated transport mechanisms to release bacteriocin. These bacteriocins have a varied spectrum of activity, mode of action and biochemical properties [4,5].